THE EFFECTIVENESS OF JIGSAW LISTENING AND PROBLEM-SOLVING TECHNIQUES TO TEACH LISTENING COMPREHENSION USING AUTHENTIC MATERIALS WITH DIFFERENT LEVELS OF ANXIETY (A CASE AT THE TENTH GRADERS OF SMA N 11 KOTA AMBON IN THE ACADEMIC YEAR 2015/2016) - Tuanany, Nurlaila; Linggar Bharati, Dwi Anggani (English Education Journal, 2017)
This study is an experimental research with a factorial design which aimed to find out the effectiveness of Jigsaw Listening and Problem-Solving techniques in teaching listening comprehension using authentic materials to the students with high and low anxiety. The samples of the study were tenth graders of SMA N 11 Kota Ambon in the academic year of 2015/2016. There were two classes, experimental class I and experimental class II which every class consisted of 20 students. Jigsaw listening technique was used in the experimental class I, while problem-solving technique was used in experimental class II. To answer research questions number one up to four, T-test was used. To answer research question number five and six, students’ mean scores in experimental class I and II were compared. While two-ways ANOVA with F-test at the 5% (0.05) level of significance was used to answer the seventh question. The result of this study showed that jigsaw listening and problem-solving techniques were effective to teach listening comprehension to the high and low anxious students. Jigsaw listening was more effective in teaching listening to the low anxious students, while problem-solving technique was more effective in teaching listening to the high anxious students. There was no interaction among jigsaw listening, problem-solving techniques, listening comprehension, and students’ anxiety.